PC-controlled scent system - E., C.Tan; Abdul Rahman, Abdul Wahab; G. , H. Goh; S., H. Wong (IEEE, 1998)
The paper describes an electromechanical system that is controlled .by a multimedia PC to press a chosen small bottle to emit scent. The scent may be from perfumes, fruits, flowers, etc., and will be related to the text information, pictures, audio and video clips presented on the PC. A user selects a scent for testing from a given set of database through a user-friendly PC-controlled window-based interface. The whole system is like an electronic information kiosk or educational kit, except that it can now provide this extra sensory information.